The operative - Britton, Andrew (New York : Pinnacles Books, 2012)
After a terror attack during a charity gala in downtown Baltimore claims dozens of innocent lives, including the wife of CIA Deputy Director John Harper, Ryan Healey is called in to investigate and is swept into an unimaginable conspiracy that suggests America may in fact be its own worst enemy.
National College of Business and Arts
Keywords: Terrorism -- Prevention -- Fiction; Thrillers (Fiction)